Grain yield response to stubble leaf blade clipping in rice ratooning in southwestern Japan - Nakano, Hiroshi; Tanaka, Ryo; Nakagomi, Koji; Hakata, Makoto (Agronomy journal, 2021)
Rice (Oryza sativa L.) ratooninghas recently attracted attention due to its higher yield potential compared with that of conventional methods. Field experiments were conducted in southwestern Japan in 2019 and 2020 to determine the effect of rice type (Hokuriku 193 and high‐yielding line [HYL]) and stubble leaf treatment (clipping and control) on the grain yields of the first and second crops in rice ratooning. In 2019, both rice types produced lower grain yields of the second crop in the leaf clipping treatment than the control treatment due to the lower spikelet number m−2. Therefore, increasing the leaf area index (LAI) in the stubble may improve the grain yield of the second crop by increasing the spikelet number per area. In 2020, HYL produced a lower grain yield of the second crop in the leaf clipping treatment than the control treatment due to the lower spikelet number m−2. However, the grain yields of Hokuriku 193 did not differ between the two leaf clipping treatments. Although the nonstructural carbohydrate (NSC) content in the stubble did not differ between the two rice types in 2019, Hokuriku 193 had a higher NSC content than HYL in 2020 due to the lower spikelet number m−2 and lower percentage of filled spikelets of the first crop. These results suggest that the stubble leaf blade contribution may be reduced when the NSC content is high as the leaf blades may compensate for the lack of NSC content when the NSC content is low. Core Ideas Stubble leaf blades contribute to the spikelet number per area. Stubble leaf blades compensate for low stubble nonstructural carbohydrate content. Early maturing cultivars are recommended to avoid lower grain filling.